2017
DOI: 10.18632/oncotarget.17270
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of VDR gene and risk of gastric cardiac adenocarcinoma in Chinese population

Abstract: Vitamin D receptor (VDR) gene polymorphisms have been reported to increase susceptibility to some malignant tumors, yet the effect on gastric cardiac adenocarcinoma susceptibility remains unknown. Here, we conducted a hospital-based case-control study to examine the correlation of single nucleotide polymorphisms of VDR rs2107301T>C, rs2228570C>T, rs1989969C>T and rs11568820 G>A and gastric cardiac adenocarcinoma susceptibility. A total 330 cases and 608 controls were enrolled in the study. Using ligation detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Polymorphisms in genes related with vitamin D metabolism, including VDR , CYP27A1 , CYP27B1 , CYP24A1 and GC , have been associated with cancer risk and progression, and may function as a valuable factor in cancer prognosis. Here, we summarized the epidemiological and genetic studies performed in recent years depicting the association of gene polymorphisms with cancer risk, progression and prognosis in Table 257, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119.…”
Section: Potentiating Vitamin D As An Anticancer Agentmentioning
confidence: 99%
“…Polymorphisms in genes related with vitamin D metabolism, including VDR , CYP27A1 , CYP27B1 , CYP24A1 and GC , have been associated with cancer risk and progression, and may function as a valuable factor in cancer prognosis. Here, we summarized the epidemiological and genetic studies performed in recent years depicting the association of gene polymorphisms with cancer risk, progression and prognosis in Table 257, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119.…”
Section: Potentiating Vitamin D As An Anticancer Agentmentioning
confidence: 99%
“…Systems biology and high-throughput screening methods have revealed that the incidence of GCA is associated with mutations in tumor protein P53 (18,19) and the vitamin D receptor (20), as well as polymorphisms in the Fas ligand gene (21) and thymidylate synthase (22). In addition, proteins such as cancer antigen 125 and minichromosome maintenance 5 serve as potential biomarkers for the early diagnosis of GCA (23,24).…”
Section: Introductionmentioning
confidence: 99%